S??ndrome de Burnout, presente??smo e a qualidade de vida no trabalho de gestores de uma institui????o judici??ria federal - Farias, Elisabete Felix (2017)
The illness and its relation to the lack of attendance or presence at work has been the focus of several studies, representing a reality that generates high costs for both public and private institutions, and especially for the worker. The objective of this study was to evaluate the correlation between quality of life in the work of managers of a federal judicial institution, presenteeism and Burnout Syndrome, work - related disorder related to absenteeism, early retirements and low productivity. This is a descriptive-exploratory case study, cross-sectional, under a quantitative evaluation, adopting multivariate statistics for data analysis. The following instruments were used: a questionnaire containing data on the sociodemographic profile and the professional profile; The QVP-35 questionnaire, to evaluate the quality of life at work; The MBI-GS inventory, to determine the occurrence of Burnout Syndrome; The SPS-6 scale, for the analysis of presenteeism. The data presented by 47 department managers of a Federal Judicial Institution, based in the city of S??o Paulo, were analyzed by means of Analysis of Variance (ANOVA), seeking to correlate the component dimensions of each of the questionnaires applied. It was observed that, in relation to the sociodemographic and professional profiles of the respondents, the relevant variable in relation to the presence or absence of Burnout Syndrome was schooling. Similarly, of the analyzed dimensions of QVP-35 versus Burnout Syndrome, the main associations were found with the variable "Work Related Discomfort". Among the significant correlations obtained between Burnout Syndrome and presenteeism, Emotional Exhaustion was evidenced as a preponderant element. The contributions of the research allowed providing important subsidies for the Administration of the Court, aiming at facing the problems identified and the formulation of quality of life policies at work with a preventive bias of health problems in the institutional scope. From the academic point of view, the research made it possible to advance in the consolidation of the approach to quality of life at work, presenteeism and Burnout Syndrome and to establish indications for new studies.